Microstructural control and characterization of CuAlNi-based SMA fabricated by continuous casting process - Jang, WY; Lee, SH; Jee, KK; Jeong, SH; Kim, KS; Lee, EG (TRANS TECH PUBLICATIONS LTD, 2002)
The microstructural changes and transformation characteristics of unidirectionally solidified Cu-13.4%Al-4.1%Ni shape memory rod, which was fabricated by continuous casting, were investigated. The effect of betatizing on the microstructure and transformation characteristics of unidirectionally solidified rod was also studied. The unidirectional grains grow preferentially in the casting direction with increasing casting speed. M-s and A(s) temperatures of the cast rod are gradually fallen with increasing casting speed. Two distinguishable beta(1)' and gamma(1)' martensites coexisted by betatizing above 873 K. As the betatizing temperature is raised up, the volume fraction of gamma(1)' martensite is gradually decreased but that of beta(1)' martensite is gradually increased while transformation temperatures are shifted to lower temperature. The fracture stress and strain of unidirectional solidified rod are 550 MPa and 36%, respectively.
Keywords: WIRES